Negotiating Safety and Wellbeing: The Collaboration Between Faith-Based Communities and Public Health During the COVID-19 Pandemic - El-Majzoub, Salam (Journal of religion and health, 2021)
The COVID-19 pandemic led to lockdown measures where congregational faith-based activities were prohibited. With time, the collateral impacts of confinement emerged as priorities, and impositions had to be balanced with the collaboration of the population. In this process, faith-based organizations played a key role in encouraging their congregations to adhere to lockdown measures while fostering their mental wellbeing and resilience. This paper describes the process of establishing a collaborative negotiation among the Montreal Regional Public Health Unit, the police, and the Muslim and Jewish communities, examining the role of mediation in this context. Despite some obstacles, such as communication difficulties and decision-making limitations, the collaborative approach seems to buffer the escalation of intercommunity tension and to promote communities’ commitment to physical distancing measures and should be considered in times of pandemic for a more inclusive public health approach.